The international primary commodity markets : key policy issues for developing countries. - MAIZELS, Alfred (1994)
Notes that the commodity price downtrend since the 1980s was almost certainly one important element in the huge rise in the foreign debt of developing countries. Identifies short term commodity policies as (1) raising depressed levels of commodity prices, and (2) reducing excessive short-term price instability. Long term commodity policies include diversification, environmental protection, reducing remaining barriers to commodity trade, and, improving the position of natural raw materials.